OCULAR COMPLICATIONS DUE TO INTRAORAL LOCAL ANESTHESIA: A CASE REPORT - Claudia Florida Costea; A.I. Cucu; Nina Earar; Gabriela Dimitriu; Cristina Dancă; Mădălina Adriana Chihaia; Dana Mihaela Turliuc (Romanian Society of Oral Rehabilitation, 2017)
Intraoral local anesthesia is a common dental procedure. It may often be accompanied by general complications, some of which may be ophthalmological, like: diplopia, ptosis, mydriasis, amaurosis, strabismus [1]. We report the case of a 67-year-old female patient who suffered an extraction of the left maxillary second molar and after intraoral local anesthesia administration she noticed the onset of diplopia, due to left lateral rectus muscle palsy. Ocular complications may occurs during intraoral local anesthesia, which are most of the times remitted and leave no visual sequelae.